UNIFIED COMMUNICATION: A SURVEY ON HARMONIZING REGIONAL LANGUAGE DIVERSITY - V, Thenarasi; B N, Santhosh Kumar; Urs M, Prakasha Raje; R, Rashmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This project tackles the complex task of extracting insights from text and images using Optical Character Recognition (OCR). After extracting text, language identification is crucial for a comprehensive multiclass classification approach, especially given the limitations of existing machine translation systems for Indian languages. The paper carefully examines challenges in machine translation, morphological analysis, parsing, word sense disambiguation, and the translation process to enhance the quality of translations. Beyond translation, the project includes automatic text summarization to distill essential content. Through the seamless integration of OCR, language detection, translation, and text summarization, our approach aims to facilitate unified communication by harmonizing diverse voices in multilingual settings